PENERJEMAHAN KOSAKAT BUDAYA BAHASA JEPANG DALAM NOVEL RAHASIA HATI KARYA NATSUME SOSEKI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the translation of Japanese cultural words in “Rahasia Hati” novel by Natsume Soseki which was translated by Hartojo Andangdjaja in Indonesian. This study aims to explain the methods and procedures of translating cultural words in the category of ecology and material culture as well as their equivalence of meaning. The method used in this study is descriptive qualitative. Data were obtained by reading and understanding novels in Indonesian and their translations into Indonesian, then writing and classifying several relevant cultural words into the categories of ecology and material culture. This study obtained 53 data on cultural words which includes 7 translation procedures used, namely transposition, modulation, adaptation or cultural equivalence, notes, contextual equivalence, transference, and functional equivalence. The translation method used tends to be oriented towards the target language.Key Words: Translation, Cultural Words, Method, Procedure, Equivalence